2006
DOI: 10.2106/jbjs.d.03018
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Steroid Use for Postoperative Pain Relief

Abstract: Despite the availability of various analgesic regimens, patient surveys have indicated that moderate-to-severe postoperative pain is still poorly managed. The use of corticosteroids for postoperative pain relief, although popular, has yet to gain wider acceptance because of concerns over side effects, in particular adrenal suppression, osteonecrosis, impaired wound-healing, and concerns about efficacy. The medical literature provides evidence that should substantially decrease these concerns with regard to low… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
120
0
15

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 190 publications
(139 citation statements)
references
References 120 publications
4
120
0
15
Order By: Relevance
“…Our findings agree with those of previous small series [15,36,38,40] and reviews of numerous perioperative settings [19,21,22,46] that found no association between corticosteroid use and increased risk for postoperative wound infection. Furthermore, studies using higher corticosteroid doses than that used in our study showed no increase in postoperative wound infection after major orthopaedic surgeries [1,5,19,25,46]. The rate of periprosthetic joint infections after primary TKA at our institute was 0.6% (8/1323 patients) between 2006 and 2009 [50], and we have maintained the same operating room environment, surgical scrub, skin preparation, and antibiotic prophylactic protocol since 2003.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Our findings agree with those of previous small series [15,36,38,40] and reviews of numerous perioperative settings [19,21,22,46] that found no association between corticosteroid use and increased risk for postoperative wound infection. Furthermore, studies using higher corticosteroid doses than that used in our study showed no increase in postoperative wound infection after major orthopaedic surgeries [1,5,19,25,46]. The rate of periprosthetic joint infections after primary TKA at our institute was 0.6% (8/1323 patients) between 2006 and 2009 [50], and we have maintained the same operating room environment, surgical scrub, skin preparation, and antibiotic prophylactic protocol since 2003.…”
Section: Discussionsupporting
confidence: 93%
“…However, all of them completed the 6-month followup visit and all were contacted by telephone to assess the presence of a periprosthetic joint infection at 1 year after TKA. Fourth, despite the numerous potential side effects associated with corticosteroids [22,45,46], we assessed only the incidence of postoperative wound complications because they are the most serious complication associated with TKA. Although previous studies using higher doses of corticosteroids reported no increase in other potential side effects [22,46], additional study is necessary to investigate potential side effects of corticosteroid use after TKA.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Dexamethasone, with an equipotent anti-inflammatory and glucocorticoid effect as betamethasone [10], has been shown to cause reduction in the incidence of PONV with a plateau effect at 8 mg [11], although other studies have demonstrated significant effects with lower doses [12].…”
Section: Introductionmentioning
confidence: 99%